Application of Gypsum Waste and Organic Fertilizer on the Growth and Yield of Peanut (Arachis hypogea L.) in Ultisol Soil - Pratama, Deni; Lestari, Tri; Febriyani, Dini (Universitas Bangka Belitung, 2025)
Peanut is an important agricultural commodity in Indonesia as a protein and vegetable oil source. Soil conditions in Indonesia are usually ultisol soils that have low pH and nutrients, this is an obstacle in peanut cultivation. This study was conducted to determine the effect of a combination of calcite sources and organic fertilizers on the growth and yield of peanut in ultisol soil. This research was conducted from May to August 2024 at UPTD Balai Benih Pertanian Air Pelempang, Bangka Regency. The research used a split-plot randomized group design. The main plot was without a calcite source (P1), agricultural calcite (P2), and gypsum waste (P3). Subplots were commercial compost (K1), chicken manure (K2), and cow manure (K3). Data analysis was performed using an analysis of variance with a significant level of 95% and a follow-up test with Duncan's Multiple Range Test with a significant level of 95%. The results showed that the treatment of calcite sources from agricultural calcite was better than the treatment of gypsum waste and without calcite sources. The treatment of organic fertilizer from chicken manure was better than cow manure and commercial compost. The combination that gave the best results with the highest value was agricultural calcite and chicken manure fertilizer, which affected all parameters except the percentage of effective root nodules, root dry weight, and flowering age. Gypsum waste has the potential to be a substitute for agricultural calcite when combined with chicken manure fertilizer, as it does not have significant results with agricultural calcite.